Risk assessment of offshore oil spill in the northern South China Sea: A stochastic scenario modeling approach - Geng, Bingxu; Zhou, Wen; Lu, Lingyan; Cao, Qian; Hong, Man; Wen, Ding (Frontiers in Marine Science, 2022)
The coastal area in the northern South China Sea (nSCS) is one of China’s most economically active regions. The fast-growing industry of marine sector and the shipping has increased the probability of oil spill accidents. An oil spill is a usually unexpected incident that is harmful to the ecological environment and marine organisms of the coastal area. As a result, utilizing a numerical model to simulate the fate and transport trajectory of spilled oil and to assess the potential risk of an oil spill accident to the coastal marine environment is of great necessity. The present study aimed to examine the impact of the risk of oil spills on the coastal environment in the nSCS. We built a hydrodynamic model and an oil spill dispersion model based on MIKE21 FM to study the tidal dynamics and oil spill dispersion in the coastal area in the nSCS. Moreover, the stochastic approach was used to simulate and predict the fastest arrival time and the probability distribution of the pollution of the oil film to the surrounding environment in the coastal regions of the nSCS. We examined the mechanisms for the influences of tides and wind on the fastest arrival time of oil film and the spatial distribution of the pollution probability of oil spill incidents at different locations in the nSCS based on the model. The results showed that the wind direction has a dominating effect on the direction of the oil dispersion. Due to the differences in the tidal dynamics in different regions, the migration and dispersion of the oil are also affected by the tidal current. This research provides guidance on the risk assessment of oil spill accidents for marine environmental management.